Mengatasi Tantangan Pengelolaan Sampah di Depok: Pendekatan Pemilahan dan Pengolahan Sampah di Masyarakat - Harahap, Elfira Febriani; Yojana, Ratna Mira; Mayusda, Idriwal; Septiani, Winnie; Astuti, Pudji (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This research on community involvement aims to provide education regarding waste sorting, training in gradual waste sorting, and processing organic and inorganic waste. Methodology: The method combines a structured process including field observations, comprehensive assistance, outreach on waste processing, discussions, and simple organic and inorganic waste sorting. Results: Before this Community Service Activity (PKM), most residents were already accustomed to sorting waste. However, only a few process it further, where only 22.2% process their waste. This training explains the types of waste, the importance of processing waste, and how to process it. After this activity, residents were enthusiastic and interested in learning to process organic and inorganic waste. After CSA activities, more residents wanted to process waste (organic: 64.3%, inorganic: 92.9%). Conclusions: The PKM successfully raised participants' awareness of the importance of waste processing beyond just sorting. Residents were interested in learning more to apply this practice and contribute to a better environment. This PKM activity needs to continue so that the community can fully implement waste sorting and processing in their surroundings. Limitations: The activities did not provide detailed waste processing practices, so the public still doubts carrying out independent waste processing. Time for activities and discussions with participants is also limited. Contribution: This activity increases residents' awareness about waste sorting and processing. The public is given knowledge about types of waste, how to sort waste, and waste processing to increase community participation in waste management.